Simulation of the Potential Liquification of Puger Sand Soil on a Small Scale in the Laboratory - Alihudien, Arief; Alfaries, M. Rifki; Rizal, Nanang Saiful (Rekayasa Sipil, 2025)
Puger is a nearshore area in the Jember district. On the Indonesian liquefaction zone atlas map, Puger is a high liquefaction zone.  Liquefaction can occur when water-saturated soil loses its strength and behaves like a liquid due to seismic vibrations. Thus, an in-depth understanding of soil behavior and the structures above it due to liquefaction events is needed to mitigate disasters.  This study aims to effectively simulate the liquefaction potential of Puger sand material on a small laboratory scale to identify soil behavior that can cause structural damage due to liquefaction phenomena. The method used in this experiment is that water-saturated sand samples are placed in a container and subjected to vibration using a shaker to simulate the effects of an earthquake. Parameters observed include changes in density, soil deformation, and pore pressure during and after vibration. The simulation results show that the pore pressure increases sharply at a certain depth, reducing the cohesion between sand grains and causing a decrease in soil strength. This can be seen from the increase in pore pressure, which automatically decreases the effective soil stress in the soil.